"We are often invisible": A survey on safe space for LGBTQ students in secondary school choral programs. (June 2018) - Palkki, Joshua; Caldwell, Paul
This article presents data from a large-scale cross-sectional survey of LGBTQ college students ( N = 1, 123) reflecting on their middle and high school experiences in choral music. The quantitative data indicate that students felt safer in high school than in middle school and that a small majority of high school teachers voiced support for LGBTQ students. These data indicate that high school choral classrooms were perceived as safe for a majority of respondents. The open-ended responses highlight themes including: the plight of transgender students who faced difficulty navigating their gender identities in the choral environment, the importance of enumerated non-discrimination policies, and the importance of words/semantics. Respondents discussed helpful and hurtful words and/or policies that influenced their choral experiences. A main theme was encouragement of open acknowledgement of LGBTQ identities and issues in the choral classroom. Suggestions for teaching practice and policy are provided based upon these data.